Penyuluhan Manajemen Kebersihan Menstruasi (MKM) Pada Remaja Putri di Desa Pungka Sumbawa - Yunita Lestari; Has’ad Rahman Attamimi (Jurnal Nusantara Berbakti, 2023)
Menstrual Hygiene Management (MHM) is the management of hygiene and health for women when they are menstruating. Users of sanitary napkins who are clean, can be changed frequently during menstrual periods, and have access to their disposal, and can access toilets, soap, and water to clean themselves in comfortable conditions with maintained privacy. The purpose of this activity is to provide health education about Menstrual Hygiene Management (MHM) for Adolescents as the Application of Behavior to Maintain Personal and Environmental Hygiene. This community service method is carried out by holding counseling in the village of Pungka. community service activities (pengabmas) regarding MHM for Adolescents as the Application of Behavior to Maintain Personal and Environmental Hygiene